The Role of Virtual Laboratory Facilities and Infrastructure in Developing Student Competence in Engineering Education - Jaya, Hendra; Haryoko, Sapto; Sabara, Edy; Mantasia; Suhaeb, Sutarsi; Saharuddin, S. (Golden Ratio of Data in Summary, 2025)
This study investigates the impact of Virtual Reality (VR)-based virtual laboratory facilities and infrastructure on students' competencies in the Department of Electronic Engineering Education at the Faculty of Engineering, Makassar State University. With the increasing integration of digital technology in education, virtual laboratories have become pivotal in enhancing students' technical and conceptual understanding, especially in technical fields such as electronics. The research employs a quantitative survey method, distributing questionnaires to 31 students. Data analysis includes descriptive and inferential statistics, including regression analysis to examine the relationship between the adequacy of virtual laboratory facilities, student motivation, and their academic competencies. The results reveal a significant positive influence of the sufficiency of virtual laboratory infrastructure and student motivation on their competencies. Specifically, the study finds that improvements in the adequacy of virtual laboratories contribute to a notable improvement in students' practical and conceptual skills. Moreover, higher student motivation correlates with better academic performance. This research underscores the importance of upgrading virtual laboratory facilities and fostering student engagement to maximize learning outcomes in technical education.